PENGARUH KOMPOSISI MEDIA TANAM (SEKAM BAKAR DAN PUPUK KANDANG KOTORAN SAPI) TERHADAP PERTUMBUHAN SEMAI JATI PUTIH (Gmelina arborea Roxb) - Yohana Fransiska Nahak; Antonius S.S Ndiwa; Mamie E Pelondo'u (Wana Lestari, 2020)
This study aims to determine the inffect of the composition of the planting media (toasty husks and cow manure) against seedling growth Gmelina arborea Roxb. The research method used in this study is a complete random design (RAL) with seven treatments and five replications. This research was conducted in January to April 2019, located in Alas Village, subdistrict of East Kobalima, Malaka Regency. The results of this study indicate that composition of organic growing media (toasty husks and cow manure) significant and very significant on plant seeds, on height growth variables, on stem diameter, number of leaves and seed quality index of Gmelina arborea Roxb. Combination treatment with a dose 35% cow manure + 50% toasty husks + 15% soil (M6) is a combination of seed planting media Gmelina arborea Roxb the best that can increase growth of seeds Gmelina arborea Roxb, with growth average 65.20 cm, diameter average 4.964 mm, number of leaves average 18, 20 and the highest seed quality index value reached 1.407.